Hypercalcaemia in malignant lymphoma. Issue 651 (January 1980) - Greaves, M.; Hancock, B. W.
Abstract : Three patients with malignant lymphoma complicated by hypercalaemia without radiological bone abnormality are described. The medical literature has been reviewed and the possible underlying mechansims discussed. The early diagnosis of this potentially fatal complication is important since this may respond (together with the underlying disease) to appropriate chemotherapy.